Canine Ocular Transmissible Venereal Tumour - A Report of Four Cases - K S, Rugmini; S, Subapriya; Raj H, Pushkin; Rao, Ganne Venkata Sudhakar; S, Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine Transmissible Venereal tumour (TVT) or Sticker’s sarcoma is a sexually transmitted neoplasm which is endemic in tropical and subtropical countries. The tumor is transmitted between dogs through direct skin contact, licking and bite injuries (Kabuusu et al., 2010). External genitalia are the frequent location for TVT. It can also occur in areas such as the oral cavity, nasal cavity, skin, sclera, and anterior chamber of the eye. Tumor cell inoculation is also possible in extragenital primary sites, such as the nasal and oral cavities, rectum, skin, and ocular membranes (conjunctiva), via licking or sniffing of the vaginal and/or the preputial discharge. TVT is further characterized by a unique feature wherein the mutated tumor cell itself acts as the causative agent and propagates within the implanted host (Ganguly et al., 2016). The present report describes the extraocular and intraocular manifestations of TVT in dogs and its response to treatment.